How could hospitality employees survive? The individual costs, career decisions and autonomy support of furlough strategies in a crisis. (September 2022) - Zheng, Chen (Jerry); Wu, Jialin (Snow); Zhao, Xinyuan (Roy)
Abstract: The hospitality industries are fragile and have very little business in a public crisis such as the Covid-19 pandemic. Under a difficult time, the hospitality organizations still need to keep talent employees who are critical when the business is recovered. Furlough that employers keep talent employees without variable cost, becomes a common choice among hotels. However, the potential impacts of such furlough practices on employees have rarely been investigated. By analyzing the data set from 386 furloughed UK hotel employees, the present study illustrated that the perceived costs of furlough as well as the availability of alternative opportunities resulted in career changes, and that feelings of acknowledged as a dimension of autonomy support weakened the effects of social costs on career change decisions. The findings call for more balanced furlough strategies and extend knowledge about social justice at workplace. Highlights: Furlough helps hospitality industries by maintaining talent employees during COVID-19 Perceived costs of furlough are positively associated with career change intentions Furlough practices need to provide employee autonomy support to trade off potential costs